Effects of Multi Strain Probiotics on Egg Production and Quality in Laying Hens Fed Diets Containing Food Waste Product - Chung, Sung Heon; Lee, Jinyoung; Kong , Changsu (International Journal of Poultry Science, 2014)
The objective of the present study was to evaluate the effects of multistrain probiotics (MP) supplementation to diets containing 40% food waste product (FWP) on egg production and quality. Forty wk-old Lohmann Brown were allocated to 4 dietary treatments with 5 replicates and 2 birds/cage in completely randomized design. A basal diet formulated to contain corn, soybean meal and FWP and 3 additional diets were prepared by adding 0.1, 0.2, or 0.4% of MP. During the 3-wk feeding period, the addition of 0.4% MP showed the least egg production (75.4%) compared with 0 (85.5%) or 0.2% (81.4%) MP addition (p<0.05), but the egg production was not different between 0.1 and 0.4% MP addition. The BW changes as well as feed intake were not different among the dietary treatments. The BD supplemented with 0.4% MP showed greatest Haugh units (60.4, p<0.05) compared with other treatments. There was no significant difference in yolk color among the treatments with the exception of dietary group with 0.4% added probiotics in which the least Roche color index (8.4, p<0.05) was observed. In conclusion, the present study indicated that the addition of probiotics to diets containing 40% FWP improved the egg protein quality but did not affect productivity of laying hens.